Migration, nursing, institutional discrimination and emotional/affective labour: ethnicity and labour stratification in the UK National Health Service - Batnitzky, A; McDowell, L (Routledge, 2011)
The UK has a long history of recruiting foreign nurses to meet labour shortages. This article explores the ways in which a combination of institutional discrimination in recruitment and promotion and daily interactions and practices in the workplace practices constructed migrant nurses as less skilled and inappropriately embodied and so restricted their overall career trajectories. Based on qualitative research with migrant nurses of Caribbean and Asian origins who came to the UK in the post-war era, we show how race and ethnicity were the basis of initial restrictions in training leading to permanent stratification in the nursing labour force. In the interactive and emotional labours of caring, foreign-born nurses are subjected to stereotypical and normative assumptions about their attributes and skills from colleagues, managers and patients that affect their opportunities to progress within the National Health Service. We thus combine an analysis of institutional discrimination with an understanding of cultural practices in the workplace to explain their disadvantaged position.